AKTA PELEPASAN HAK PAKAI DALAM PERJANJIAN TUKAR MENUKAR ANTARA PEMERINTAH DENGAN PIHAK SWASTA: Hayyun Indy Kurniawan - admin, admin (Reformasi Hukum, 2017)
The content of the agreement in both the Provincial Government and private parties should clearly indicate the contents of the agreement to be able to obtain their own right. Agreement by the parties can be called the agreement under the arms so that when problems arise in the future, the private sector is quite difficult to prove. The method used in this study is a normative legal research. The result of this research is the Rule of Law Implementation Deed of Waiver to Use Public of the Treaty Swap between the Government and the Private Sector in the release of right to Use Public frequently experience barriers to judicial since the company will acquire the land is not the subject of property rights, so the way to do is by way of a waiver. Once the waiver is done then the land is state land status and continued with rights application filed at the National Land Agency where land was then given to the new rights to guarantee legal certainty.